Nutritional composition and antioxidant potential of monkey pineapple (Myrianthus arboreus) fruit pulp and seeds from Cameroon Eastern forests - Ulrich Landry Kamdem Bemmo; Jean Marcel Bindzi; Chancel Hector Kenfack Momo; Serge Cyrille Houketchang Ndomou; Willy Nelson Matike Ekwelle; Stephano Tene Tambo; François Ngoufack Zambou (Heliyon)
The aim of this work was to determine the nutritional value and antioxidant potential of the pulp and seeds of the fruit of Myrianthus arboreus grown and consumed in the Eastern Region of Cameroon. The physicochemical and nutritional analyses of the pulp and seeds showed that the water content ranged from 89.33 to 95.05 % of the fresh matter, the ash from 2.55 to 2.45 % of the dry matter, the pH from 4.50 to 6.10 and the total titratable activity from 76.15 to 9.92 meq/100 g of dry matter. As for the mineral salts, the maximum contents of Ca, Na, Fe, Mg, Zn, K, and Cu were found in the different samples. Regarding the macronutrient composition, we obtained 42.40 and 39.65 % of carbohydrates, 20.96 and 41.61 % of proteins, 6 and 7.06 % of lipids, and 16.13 and 4.27 % of fibers for the pulp and seeds, respectively. The hydroethanolic extract is the best-interacting reagent on the mesocarp and endocarp of M. arboreus, presenting respectively the highest content of total phenolics (36.27 and 30.26 mg EqAG/g extract) and flavonoids (13.48 and 8.1 mg EqCAT/g extract). The best capacity to scavenge the DPPH radical, the best capacity to inhibit the hydroxyl radical and the best-reducing power of ferrous ions were also observed in the hydroethanolic extract of each sample (pulp and seeds) with an efficient concentration 50 of 83.17 and 6760 μg/mL respectively. The fruit of M. arboreus could improve the nutritional status of Eastern Cameroonians based on the results obtained.